Analisis Teori Produksi Dalam Perspektif Islam - Daulay, Raihanah; Inayah Siregar, Hilyati; Harahap, Isnaini (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2024)
Production theory becomes the most important part to be studied in meeting individual needs for goods. However existing production has not been able to meet the needs of each individual, so uneven production causes many regions to lack food and other needs. This study aims to analyze how Production Theory is about the sustainability of domestic production. This research is a literature research with descriptive qualitative analysis. Data sources are obtained through searching internet sources in the form of Qur'an and Hadith sources, books, national and international articles, and online news.  The analysis technique used is content analysis which focuses on the perspective of Islamic economics.  This study concludes that the theory of production in conventional economics is based on the Homo Economicus paradigm independent of moral guidance. However, Production Theory from an Islamic perspective is based on the Homo Islamicus Paradigm which implements the objectives of sharia (maqashid sharia). In maintaining the sustainability of domestic production, this study recommends maintaining production factors through environmental sustainability, fulfilling labor rights, and using domestically produced raw materials.